PHENOMENOLOGICAL STUDY ON THE PROCESS OF PREPARING THE LOCAL GOVERNMENT WORK PLAN (RKPD) IN LEMBATA REGENCY - Wukak, Maria Fransiska Ure; Supriyono, Bambang; Wike, Wike (Faculty of Administrative Science, Universitas Brawijaya, 2024)
This study aims to describe and analyze the unique experiences, understandings, and meanings of planners in the process of preparing the Local Government Work Plan (RKPD) in Lembata Regency. The method used is qualitative phenomenology. The data analysis technique uses Interpretative Phenomenology Analysis (IPA). The results show that the planners' experiences include: inconsistent planning processes, planning without work guidelines, planning without commitment, and partial planning. The planners' understanding is planning oriented towards process and output. Unique interpretations include loyalty to the planning organization, awareness of the mismatch between planning and budgeting, interpreting planning as the basis for development, and the need for strategies to improve the work system. In response to this, for future planning, the Lembata Regency planning agency needs to do several things, including increasing understanding of basic matters such as organizational structure of work procedures and planning rules, developing planning guidelines and standard operating procedures for planning, collaborating process and substance approaches in preparing planning documents, strengthening coordination, increasing the capacity of planning resources, and implementing a merit system in transfers and rotations within the planning agency.